Government Strategy in Developing Sustainable Tourism in Palippis Beach, Bala Village Polewali Mandar Regency - Nawawi, Juanda; Rusli, AM; Izzah, Nurul (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This research is motivated by the importance of sustainable tourism development strategies that are not only oriented towards increasing tourist visits, but also on environmental conservation and community involvement. The purpose of this study is to analyze the government's strategy in developing sustainable tourism at Palippis Beach, Bala Village, Polewali Mandar Regency, and to map the actors involved. This study uses a descriptive qualitative approach with data collection techniques such as observation, interviews, and documentation studies. Data analysis refers to Geoff Mulgan's five strategies: goal setting, environmental analysis, direction, action, and learning. The results show that the government's strategy includes guidance, development of facilities and infrastructure, promotion, and community involvement through the Tourism Group (Pokdarwis). Government actions are adjusted to the field situation, including security obstacles, and are carried out through a communicative approach. The study's conclusions demonstrate the importance of collaboration between the government and local communities in supporting tourism sustainability. The novelty of this study lies in the integration of development strategies with a non-interventionist approach and actor mapping that emphasizes the strategic role of local communities as primary managers. These findings contribute to the formulation of community-based sustainable tourism policies.